2022
DOI: 10.3389/fpubh.2022.893673
|View full text |Cite
|
Sign up to set email alerts
|

Examining Primary Care Physicians' Intention to Perform Cervical Cancer Screening Services Using a Theory of Planned Behavior: A Structural Equation Modeling Approach

Abstract: BackgroundPromoting cervical cancer screening (CCS) is undoubtedly effective in combating severe public health problems in developing countries, but there are challenges to its implementation. Understanding the factors influencing primary care physicians' intentions to provide CCSs to rural women is crucial for the future implementation of screening programs. The aim of this study was to assess the intentions of primary care physicians to provide cervical cancer screening services (CCSSs) to rural women and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
(68 reference statements)
1
1
0
Order By: Relevance
“…All hypotheses in the model were supported, confirming that TPB is an acceptable theoretical basis for this study. This finding is consistent with previous TPB-based studies conducted in the United States (80), China (81,82), and Europe (57).…”
Section: Discussionsupporting
confidence: 93%
“…All hypotheses in the model were supported, confirming that TPB is an acceptable theoretical basis for this study. This finding is consistent with previous TPB-based studies conducted in the United States (80), China (81,82), and Europe (57).…”
Section: Discussionsupporting
confidence: 93%
“…Even more remarkable, it revealed that the correlation between behavioral attitudes, subjective norm, and perceived behavioral control was significantly greater in subordinate hospitals than in the leading ones. Given the disparity in financial support and medical resources between leading and subordinate hospitals within Chinese medical consortiums, especially subordinate hospitals in resource-poor areas confronted with constraints of fewer organizational resources and lower individual capabilities [ 50 ], medical staff in subordinate hospitals had fewer types of health technologies to choose, which would probably make them rely more on specific technologies and also tend to develop common beliefs toward regarding technologies [ 51 ].…”
Section: Discussionmentioning
confidence: 99%